PENGARUH KETERLIBATAN KERJA DAN LOYALITAS KARYAWAN TERHADAP KINERJA KARYAWAN (PADA KARYAWAN BANK UOB CABANG PEKANBARU) - Fitri Afriani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
United Overseas Bank Limited (UOB) is engaged in the banking field. UOB Bank is a leading bank in Asia which provides a large number of financial services through its global network. In order to face the competition is quite tough, and able to survive even in difficult circumstances and to provide the best service to its customers the company should pay attention work engagement and loyalty of employees to increase their involvement and awareness and loyalty of employees to work in this company and also to find out how employee performance. To that effect we perform research work engagement (X) and employee loyalty (X2) on employee performance (Y). The method in this research is quantitatively using SPSS program 17, where samples were used that employees with respondents as many as 40 people. The sampling technique is probability sampling. The results showed that the results of hypothesis testing T test, t is known t arithmetic (6.329)> t table (2.024) and sig (0.000) <0.005. meaning that job involvement variables significantly influence employee performance. t (6.739)> t table (2.024) and sig (0.000) <0.005 means that the variable employee loyalty significant effect on employee performance.Keywords: work involvement, employee loyalty, employee performance